2017
DOI: 10.1073/pnas.1619726114
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the PBRM1 tumor suppressor gene amplifies the HIF-response in VHL −/− clear cell renal carcinoma

Abstract: Most clear cell renal carcinomas (ccRCCs) are initiated by somatic inactivation of theVHLtumor suppressor gene. TheVHLgene product, pVHL, is the substrate recognition unit of an ubiquitin ligase that targets the HIF transcription factor for proteasomal degradation; inappropriate expression of HIF target genes drives renal carcinogenesis. Loss of pVHL is not sufficient, however, to cause ccRCC. Additional cooperating genetic events, including intragenic mutations and copy number alterations, are required. Commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
133
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(162 citation statements)
references
References 30 publications
(47 reference statements)
22
133
0
2
Order By: Relevance
“…4A and table S5, A and B). As expected, the hallmark hypoxia gene set was up-regulated in A704 BAF180−/− vs. A704 BAF180wt cell lines (family-wise error rate - FWER q=0.071) (table S5A) (19). Across the more refined “founder” gene sets describing these five significantly enriched hallmark gene sets, the most strongly enriched gene set in PBAF-deficient cell lines was the KEGG cytokine-cytokine receptor interaction gene set (FWER q=0.0020 for A704 BAF180−/− vs. A704 BAF180wt and q=0.023 for A704 BAF180wt, BRG1−/− vs. A704 BAF180wt ) (Fig.…”
supporting
confidence: 72%
See 2 more Smart Citations
“…4A and table S5, A and B). As expected, the hallmark hypoxia gene set was up-regulated in A704 BAF180−/− vs. A704 BAF180wt cell lines (family-wise error rate - FWER q=0.071) (table S5A) (19). Across the more refined “founder” gene sets describing these five significantly enriched hallmark gene sets, the most strongly enriched gene set in PBAF-deficient cell lines was the KEGG cytokine-cytokine receptor interaction gene set (FWER q=0.0020 for A704 BAF180−/− vs. A704 BAF180wt and q=0.023 for A704 BAF180wt, BRG1−/− vs. A704 BAF180wt ) (Fig.…”
supporting
confidence: 72%
“…The PBAF complex suppresses the hypoxia transcriptional signature in VHL −/− ccRCC (18, 19) but its effects on tumor-immune interactions have not been thoroughly studied. To explore the potential impact of this complex on the immunophenotype of ccRCC, we analyzed previously reported whole transcriptome sequencing (RNA-seq) data from A704 ccRCC cell lines with perturbations in the PBAF complex (19). Loss of BAF180 or the related PBAF subunit BRG1, encoded by the gene SMARCA4 , prevent formation of the intact PBAF complex (19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Besides VHL, mutations in other genes such as PBRM1, SETD2, ARID1A, SMARCA4, JARID1C, and KDM6A/UTX have been reported in ccRCC (47,85), and these are likely to augment VHL's core transcriptional effects (86), contributing to heterogeneity in disease phenotypes (87) and progression patterns (88). Using the example of 786-O cells, at least two other mutations in these cells may have a direct impact on chromatin-MLL3 (p.A3902G) and gain-of-function TP53 mutations (p.R248W).…”
Section: Discussionmentioning
confidence: 99%
“…Varela, et al demonstrated that suppression of PBRM1 through siRNA resulted in enhanced proliferation, colony formation, and migration of several ccRCC cell lines in vitro , consistent with a tumor suppressive function in renal carcinoma [38]. Interestingly, Gao, et al did not recapitulate these in vitro findings, but found that PBRM1 suppression by CRISPR did promote subcutaneous tumor growth in an on-target fashion [39]. Inactivating or truncating mutations in JARID1C (also known as KDM5C ), a histone H3 lysine 4 demethylase, and UTX (KMD6A) a histone H3 lysine 27 demethylase were identified in another study as positively selected for in ccRCC compared to other cancers [40], [41].…”
Section: Genetics Of Ccrccmentioning
confidence: 99%